Uso e características dos fragmentos florestais urbanos da cidade de Manaus/AM - (:unkn) unknown (Universidade Federal do Amazonas, 2008)
The main goal of this study is to relate FFUs spatial distribution and area with the characteristics as of avocation from the city. 56 FFU were identified ranging in size between three and 578.6 hectares. Regarding the property regime 26 FFU were private and 30 were public land. Preliminary results on the status of property (private = 1; public = 0) showed significant relationship between the status and FFU areas. Six categories of FFU occupation were identified in the urban areas surroundings the fragments. The FFU varied 17 to 90 years in agreement to the history of the city expansion and producing FFU from 2.25 to 14.88 km from city downtown and the distance of these fragments as far as the city centre variation 2.25 the one 14.88 Km. The relation between human population and natural resources listed 32 uses in four fragments: UFAM, SUMAÚMA, SESI an MINDÚ, separated in customs and socials uses. The use curve of accumulation based in participatory diagnostic, interviews did not establishment and suggest there are another uses did not related, whereas that must add in around 40 customs. The most diversity were in SESI, as well as richness and dominance, and suggests that did not relation between area and uses in fragments.
Keywords: Fragmentos Urbanos; Manaus; Processos Históricos; Populações Humanas; Recursos Naturais; Conservação; Urban Fragments, Manaus, Historical Processes, Human Populations, Natural Resources, Conservation; CIÊNCIAS AGRÁRIAS